Systemic clinical outcome and routine evaluation - family of origin (score-15-fo): validation studies in a sample of portuguese lgb young adults - Lourenço, Ana da Silva (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação